ARCHAEOLOGICAL RESEARCH AT THE TASTAK CEMETERY IN 2023 (ABAI REGION, URZHAR DISTRICT) (Journal of history-rus, 2024)
The article introduces for the first time the results of archaeological research at the Tastak cemetery in the field season of 2023, located in the southern foothills of the Tarbagatai Range. The mentioned region in archaeological terms is a little-studied region. In the process of field stationary works, reconnaissance of the area was carried out and a topographic plan of the cemetery was taken. Two kurgans (no. 7 and no. 11) were investigated during this period. According to the planographic arrangement of the sites, the structure of the overmound and intra-mound construction, as well as the position and orientation of the burials corresponds to the classical Saka period. Some constructive features of the structure were revealed: stone shell, grave fence. The noted constructive features of the construction can be connected with ancient migration processes in this period. In the course of comparative-typological analysis, which includes a versatile characterisation of the archaeological source, identification of dated analogies, as well as 14C radiocarbon AMS dating, the investigated sites are generally placed in the IV century BC. Despite the fact that the burials were looted earlier, the materials we obtained during the study of the site will certainly make a great contribution to the study of material and spiritual culture of the Saka tribes of East Kazakhstan.Key words: East Kazakhstan, Tarbagatai Ridge, Tastak, cemetery, Early Iron Age, kurgans.